1999
DOI: 10.1080/00039899909603369
|View full text |Cite
|
Sign up to set email alerts
|

Blood Lead Level and Blood Pressure During Pregnancy in South Central Los Angeles

Abstract: In many studies in which the relationship between blood pressure and blood lead level has been examined, investigators have found significant--but small--associations. There was only one previous report of a significant association of blood lead with blood pressure in pregnant women. We measured blood lead level and sitting blood pressure of 1,627 women in their third trimester of pregnancy. We eliminated subjects with known causes of hypertension. Most women (98.4%) were normotensive. We controlled for body m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…41 Furthermore, racial differences in bone metabolism and, specifically, in bone handling of lead may contribute to this apparent discrepancy in the association between blood lead level and elevated BP. 45 Blacks might also be more sensitive to the effects of lead exposure on BP owing to environmental and genetic factors. Residual confounding due to factors related to social-economic status might also contribute to a stronger association among blacks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…41 Furthermore, racial differences in bone metabolism and, specifically, in bone handling of lead may contribute to this apparent discrepancy in the association between blood lead level and elevated BP. 45 Blacks might also be more sensitive to the effects of lead exposure on BP owing to environmental and genetic factors. Residual confounding due to factors related to social-economic status might also contribute to a stronger association among blacks.…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies have suggested that blood lead is more strongly related to elevated BP and hypertension in women compared with men. 6,28,33,36,45,46 Both environmental and occupational exposure to lead has long been associated with hypertension and renal disease. 1,4,17,18,47,48 Animal studies suggest that even low levels of exposure to lead can result in hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…In four studies 31,38,65,74 the association size was reported separately for whites (n = 15 911) and nonwhites (n = 6035). For white subjects the association was 0.4 mm Hg (CI: −0.7 to +1.5 mm Hg; P = 0.26) for systolic pressure and 0.2 mm Hg (+0.1 to +0.3 mm Hg; P Ͻ 0.001) for diastolic pressure.…”
Section: Summary Statisticsmentioning
confidence: 99%
“…As well our results agree with kasper, et al [11] [12] [13] who they found that the lead level in the serum was positively associated with systolic and diastolic blood pressure. Meanwhile explained Rothenberg et al and Mitra et al [14] [15] found significant positive association between lead level and blood pressure in pregnant women. This is what was said kasper, et al [11] [12] [13] as explained the pregnant women exposure to lead from breathing the air contaminated by leaded gasoline which found in the roads.…”
Section: Resultsmentioning
confidence: 99%